(untitled) (Research, Society and Development, 2020)
Rabies is an anthropozoonosis caused by a virus that is transmitted through contact with saliva mainly through biting or mucosal licking. The objective of this study was analyze the vaccination coverage against rabies in the city of Jatai- GO from 2010 to 2018. Using data provided by the Zoonoses Surveillance Unit (UVZ) of the municipality, it can be observed that in 2010 there was no calculation for lack and in the years 2011 and 2015 there was no vaccination. In the years 2012, 2013 and 2014, vaccination coverage was 85%, 99% and 116%, respectively, and after that growth there was a decrease in coverage in 2016, 2017 and 2018, where vaccination coverage of 107 %, 107% and 98%, respectively. With this study it can be verified that the number of vaccinated animals in each year reached the goal recommended by the World Health Organization (OMS), which is 80% of the total population of animals in the municipality, but this raises the question about the accuracy of the data, since other studies show that the estimated animal population for the campaigns is well below the real value, because the municipality doesn’t have a precise survey, only an estimated number. In Jataí, although there were 13 suspected cases of rabies in chiroptera, in the range analyzed in 2014 (4 cases), 2015 (1 case), 2016 (2 cases), 2017 (3 cases) and 2018 (3 cases), all samples sent to LACEN had negative results.